Retrospective analysis of the prevalence and incidence of caries in the distal surface of mandibular second molars in British military personnel. Issue 2 (February 2017) - Pepper, T.; Grimshaw, P.; Konarzewski, T.; Combes, J.
Abstract: Mandibular third molars are commonly removed because of distal caries in the adjacent tooth. To find out the prevalence of distal caries in mandibular second molars we retrospectively studied the primary care dental records of 720 British military personnel (653 men and 67 women) from various centres. These records are standardised and personnel are required to attend for inspection regularly. Those who had been under 20 years of age at enlistment, who had served for at least five years, and had five recorded dental inspections, were included. The median (IQR) period from the first to last inspection was 15 (9.7 – 19.2) years, and inspections were a median (IQR) of 14.1 (12.8 – 15.8) months apart. A total of 59/1414 (4.2%) mandibular second molars developed caries in their distal surfaces. This was 4% higher when they were associated with a partially-erupted mandibular third molar than when associated with one that was fully erupted or absent (29/414 (7%) compared with 30/1000 (3%); p = 0.001). Carious lesions developed in the distal aspect of 22/133 mandibular second molars (16.5%) that were adjacent to a mesioangularly impacted third molar. Of these, 19/22 were successfully restored. Four mesioangularly impacted mandibular third molars would have to be extracted to prevent one case of distal caries in a second molar (number needed to treat = 3.25). Second molars that are associated with a partially-erupted mesioangular mandibular third molar have a higher risk of caries, and this can be reduced by removal of the third molar. However, distal caries in second molars seems to be a treatable and slowly-developing phenomenon and we recommend that the merits and risks of the prophylactic removal of third molars should be discussed with the patient, who should have long-term clinical and radiographic checks if the tooth is retained.